Predicting haemoglobin level within 6 hours and after 24 hours after a caesarean section: are there such formulas to calculate them? - Mohd Ariff@Ghazali, Nazhan Afeef; Ali, Saedah; Ab Mukmin, Laila (Malaysian Society of Anaesthesiologists, 2021)
Background: We measured Haemoglobin (Hb) levels within 6 hours and after 24 hours in 134 Caesarean Section cases in Hospital Universiti Sains Malaysia in 2017.